Multimedia Pembelajaran Interaktif Berbasis Game Edukasi Sebagai Media Pembelajaran Materi Sistem Peredaran Darah Kelas XI SMA Islam Az-Zahrah Palembang - Safira, Siti; Laila, Ema; Putra, Rian Rahmanda (Teknik Komputer Politeknik Negeri Sriwijaya, 2024)
The circulatory system is a material that is considered difficult to understand because it is impossible to directly see the organs and processes that make it up. Interactive multimedia acts as a learning tool. This research aims to create interactive multimedia facilities based on educational games that can be used as learning aids. This research uses the Multimedia Development Life Cycle (MDLC) Method. The stages in this research consist of Concept, Design, Material Collecting, Assembly, Testing, and Distribution. To determine its validity, the media is validated by media experts and material experts using an instrument in the form of a media suitability validation questionnaire. Aspects measured for material validity include aspects of suitability of content, aspects of suitability for use, aspects of appearance and language, aspects of presentation, and aspects of benefits. Meanwhile, media validity includes aspects of design layout, typography, illustration images, audio, presentation, use and navigation. The research results show that the average validation score for material experts is 95% to 98% and the average score for media experts is 91% to 93%. Overall the average for both is 91% to 98% and is classified as very good.Meanwhile, the results of testing on student respondents obtained a validity value of 91.48% in the very good category and managed to get a reliability result of 0.737 and can be said to be reliable. So, it is concluded that this interactive multimedia based on educational games is suitable for use as learning media in class XI SMA on the Circulatory System material.